Стратегические элиты и расширение Европы: российский вопрос - Уайт, С. (Социология: теория, методы, маркетинг, 2008)
The paper is based on research conducted for the project “Inclusion without Mem bership? Bringing Russia ., Ukraine and Belarus closer to ‘Europe’” founded by the UK Economic and Social Research Council. The author focuses on Russian foreign policy and those who influence it. In this context he had founded the most useful to speak of three key segments of Russian elites: ‘Liberal Westernians’, ‘Pragmatic Nationalists’, and ‘Fundamentalist Nationalists’. First, ‘Liberal Westernians’ favour a market economy, a democratic political system and a pro-Western foreign policy. Second, ‘Pragmatic Nationalists’ which views were first developed in the early 1990s as a critique of the pro-Westernism and have since become dominant. They do not entirely reject the views of Liberal Westernians, and they favour democracy, if not necessarily in the form in which it is understood in the West. Third, ‘Fundamentalist Nationalists’ are at the opposite end of the foreign policy spectrum and combine a strong commitment to what they regard as uniquely Russian qualities and a desire to re-establish Russian hegemony in the post-Soviet space with the antipathy to market economy. The main conclusion is that there are long-term continuities in Russian foreign policy, stemming in part from objective geographical and other circumstances. The tactical changes are rather apparent, reflecting such developments as consolidation of a powerful presidency and an increase in the salience of Russia’s natural resources for its place in the international community. There are clear associations between foreign policy stances and the variety of interests that shape Russia’s post-communism foreign policy. Besides political parties which are associated with particular stances, there are business associated with Pragmatic nationalists, and Orthodox Church with a more Fundamentalist position. It is also clear that presidency may be best seen as ‘balancing’ element, avoiding an exclusive commitment to either extreme.